The impact of Sukuk on issuer's performance in Gulf Cooperation Council (GCC) countries / Siti Fatimah Ahmad - Ahmad, Siti Fatimah (2013)
Islamic financial industry is the foundation of an economy in every country. Thus, this study aims to the factors give impact to die Sukuk issuer's performance in Gulf Cooperation Council (GCC) countries by looking from the financial statement that might have influence on Sukuk issuer's performance. Data was collected over the period of 2005 to 2011, with the study focusing on organization that used Sukuk part of their operations in GCC countries. These factors are strength of the organization, organization overall efficiency and profitability ratio. At the same time, the Sukuk issuer's performance of those issuers is questioned due to stiff competition in the Sukuk market. This study is conducted to see the sukuk issuer performances in GCC's country that are shown not growing rapidly as compared to Malaysia as countries dominated sukuk market all over the world which has Muslim population less than population in GCC's countries. Based on descriptive analysis, the study found that organization overall efficiency can give impact to the Sukuk issuer's performance. This study also revealed that, in general, Sukuk does not give big impact to the performance of Sukuk issuer's organization.